P-333 The influence of hormonal stimulation on uterine peristalsis measured by ultrasound speckle tracking in women with IVF/ICSI treatment compared to normal ovulating women. (30th June 2022) - De Boer, A; Rees, C; Blank, C; Huang, Y; Wessels, B; Wagenaar, L; Van Vliet, H; Huppelschoten, D; Zizolfi, B; Foreste, V; Di Spiezio Sardo, A; Christoforidis, N; et al.
Abstract: Study question: To investigate possible effects of ovarian stimulation during IVF/ICSI on uterine peristalsis features using ultrasound speckle tracking compared to normal ovulating women. Summary answer: Patients with a normal uterus treated with exogenous hormones during IVF/ICSI treatment show significantly increased contraction amplitude and power parameters compared to normal ovulating women. What is known already: Uterine peristalsis plays a role in procreation. Subjective visual inspection of uterine peristalsis is extensively researched throughout the menstrual cycle. Studies on uterine peristalsis in IVF/ICSI patients show higher frequency of uterine contractions during the periovulatory phase. Recently, a new automated quantitative method was validated to objectively analyse uterine strain using speckle tracking. Besides objective insight in frequency, also information on amplitude, power and coordination of motion is available. The effect of exogenous hormones on uterine contraction features has not objectively been studied using this new method. Study design, size, duration: This multicentre prospective observational cohort study was performed between 2020 and 2022 in the Catharina Hospital in Eindhoven, the Netherlands, Embryolab Fertility Centre in Thessaloniki, Greece and University of Naples, Federico II in Naples, Italy. 30 normal ovulating patients served as controls. The primary outcomes were the contraction features frequency, amplitude, direction, velocity, power and coordination in women undergoing IVF/ICSI on the day of follicle aspiration compared to controls on cycle day 9 – 14. Participants/materials, setting, methods: 19 women undergoing IVF/ICSI were included regardless of the treatment cycle number and stimulation protocol. Indication for IVF/ICSI treatment was male subfertility (n = 8), idiopathic subfertility (n = 5), tubal factor (n = 2), primary ovarian insufficiency (n = 2) or combined (n = 2), all women had normal uteri on transvaginal ultrasound. The control group consisted of 30 healthy pre-menopausal women with normal uteri on ultrasound and spontaneous regular cycles. Main results and the role of chance: Each patient underwent a 2.5 – 4 minute transvaginal ultrasound of the uterus in mid-sagittal plane. The various contraction features were extracted using a quantitative dedicated speckle tracking algorithm analysis studying motion of the subendometrial junctional zone. Mean age of IVF/ICSI patients was 32.7 years and mean BMI was 25.6. Mean age of healthy controls was 33.8 years, BMI was 23.4, and cycle length was 27.44 days. Characteristics of IVF/ICSI patients and healthy volunteers showed no statistically significant differences. Both groups predominantly consisted of nulliparous women. In IVF/ICSI patients the contraction amplitude was significantly higher compared to controls (0.062 vs 0.040; p < 0.001). The contraction power (combination of amplitude and frequency) appeared to be significantly higher in IVF/ICSI patients compared to controls (1528.18 vs 683.44; p < 0.001). No significant differences were found in contraction frequency and coordination. Even though the mean coordination did not show statistically significant differences, the values were less scattered in IVF/ICSI patients, with a much smaller range of coordination values (1.04 – 3.06) compared to healthy volunteers (1.02 – 50.33). Limitations, reasons for caution: The reported difference between IVF/ICSI patients and controls in contraction amplitude and power may not solely be attributed to the administration of exogenous hormones. The difference may also be due to an underlying cause for infertility in these patients. Another limitation of this study is the small sample size. Wider implications of the findings: Future research should explore which uterine contraction profile is associated with viable pregnancy: during the natural menstrual cycle, or when treated with hormones. The question arises whether it is preferred to transfer the embryo in the stimulated cycle or implement a freeze-all policy and transfer during the natural menstrual cycle. Trial registration number: NCT02310802